Efektivitas Edukasi Gizi Berbasis Digital Melalui Peer-group dalam Pencegahan Anemia pada Remaja Putri: Efektivitas Edukasi Gizi Berbasis Digital Melalui Peer-group dalam Pencegahan Anemia pada Remaja Putri - Fatima Rima Andini; Lina Agestika (Amerta Nutrition, 2022)
Background: Anemia among adolescents is a global health problem, including Indonesia. The prevalence of 32% made anemia a severe public health problem. Giving Blood-Boost Tablets becomes less effective when adolescents do not consume them regularly. Adolescents are easily exposed to digital-based communication through WhatsApp and video conferencing. The peer group communication method is considered effective as an innovative effort to reduce anemia among adolescents. However, its effectiveness through long-distance communication needs to be analyzed. Objectives: This study aims to identify the effectiveness of digital-based peer-group nutrition education through Whatsapp groups and video conferencing on the knowledge, attitudes, and compliance to Fe consumption among adolescent girls. Methods: This is quasi-experimental study with non-randomized pre-test and post-test control group design in 2 SMP Arjawinangun District, Cirebon involving 70 respondents (treatment n=35, control n=35). Data collection was through observation, interviews, and questionnaires. Statistical analysis used the Chi-Square Test and Wilcoxon Test. Peer educators receive training for 4 weeks from authors online, then education on anemia nutrition and blood-boosting tablets through peer groups for 3 weeks in the WhatsApp group and fe supplementation. Results: The results showed a difference in adolescent knowledge (p = 0,001; mean value: 21,7) and compliance with blood-boosting tablet consumption (p = 0,008; mean value: 0,2) among the intervention group. However, there is no difference between the control and intervention groups on knowledge (p=0.127), attitudes (constant variance value), and compliance (p=0.306). Conclusions: Education through peer groups could be more effective to prevent adolescent anemia when conducted for more than 1 month.